DAMPAK RADIASI TERHADAP KESEHATAN PEKERJA RADIASI DI RSUD ARIFIN ACHMAD, RS SANTA MARIA DAN RS AWAL BROS PEKANBARU - Mayerni Mayerni; Adrianto Ahmad; Zainal Abidin (Jurnal Ilmu Lingkungan, 2013)
Cultural safety is an important issue and should be targeted to be realized. This studyaims to determine the radiation dose and the results of medical examinations ofworkers working in the field of radiation during radiation at District General HospitalArifin Achmad Hospital Santa Maria and the Awal Bros hospital Pekanbaru. This typeof research is a kind of quantitative and qualitative research through a thematicapproach to correlation and analysis. Sampling technique using simple randomsampling as many as 39 people. Data analysis using correlation and Collaizi. Theresults of the 39 respondents indicating that the radiation workers in some PekanbaruCity Hospital RESULTS majority of radiation dose exposure in the normal categorywhich totaled 39 people (100%) from 2008 to 2011. For respondents leukocyte levels inthe normal range in the period of 2008 as many as 36 people (92.7%), in 2009 as manyas 38 people (97.4%), in 2010 as many as 38 people (97.4%), and in 2011 as manyas 35 people (89.7%). Statistically there is a weak correlation between radiationexposure to changes in the levels of leukocytes. It is characterized by the discovery ofradiation workers against health problems while working at the hospital. Mostrespondents have implemented radiation protection in accordance with the principlesof radiation protection such as the use of PPE, fillm badge, apron and to theenvironment in some Hospitals already use sunscreen with a protective layer of lead(Pb) and have been using glass-coated monitor lead (Pb).